Implementation Of Accreditation Follow-Up Management (IAFUM) To Enhance Vocational High School Education Quality (Descriptive Study Of SMK XYZ In Bandung City) - Roro Vemmi Kesuma Dewi , R.; Zahro , Mariatuz; Yulistiana, Ika (International Journal of Educational Research & Social Sciences, 2023)
This research identifies key post-accreditation issues in Vocational High Schools (VHS/SMK), highlighting low awareness of educational quality, limited involvement in planning, and a mismatch between SMK graduate skills and industry needs. Busy schedules hinder evaluating accreditation outcomes, delaying improvements and re-accreditation preparations. The study applies Corrective Action, Preventive Action, and Continuous Improvement concepts aligned with ISO 9001:2015. It analyzes Accreditation Follow-up Management's (IAFuM) impact on SMK XYZ in Bandung, employing a descriptive qualitative method. Accreditation, crucial for program eligibility, operates independently based on open criteria and government regulations. Findings reveal that while IAFuM was executed at SMK XYZ with documented planning, implementation, and evaluation actions, no records of the Inventory of Problems Resulting from Accreditation (IPRA) were found. The School Self-Evaluation based on National Education Standards (NES) and the School Quality Management System (QMS) lacked documentation. Post-IAFuM implementation, improvements in teaching processes, educator competency, administrative services, community participation, and industry collaboration were observed. However, not all schools saw enhanced alumni absorption or national exam scores. Insufficient follow-ups such as corrective actions, preventive measures, and sustainable enhancements were noted.Recommendations to boost education quality at SMK XYZ Bandung include: schools and accreditation teams reviewing issues, integrating IAFuM with QMS, policymakers considering IAFuM for accreditation gaps and school mentoring, and Accreditation Body for School/Madrasa (AB-S/M) including accreditation result records in school certificates.